2004
DOI: 10.4049/jimmunol.173.12.7183
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Cryptopatch Formation in Mice Requires Lymphotoxin α and the Lymphotoxin β Receptor

Abstract: Interactions between lymphotoxin (LT)α1β2 on inducer cells and the lymphotoxin β receptor (LTβR) on stromal cells initiate development of lymph nodes and Peyer’s patches. In this study, we assessed the contributions of LTα and LTβR to the development of cryptopatches (CP), aggregates of T cell precursors in the mouse small intestine. Mice genetically deficient in LTα or LTβR lacked CP. Bone marrow from LTα-deficient mice was unable to initiate development of CP or isolated lymphoid follicles (ILF) after transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 34 publications
2
68
0
Order By: Relevance
“…Previous reports showed that ILF and CP can be induced in lymphotoxin ␣ mutants lacking such structures by transplantation with wild-type bone marrow (13,26). We therefore generated bone marrow chimeras using wild-type and CCR7-deficient mice as recipients and/or donors and analyzed the phenotype of SILT 7-9 wk after reconstitution.…”
Section: Bone Marrow Reconstitution Induces/reverts the Phenotype Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that ILF and CP can be induced in lymphotoxin ␣ mutants lacking such structures by transplantation with wild-type bone marrow (13,26). We therefore generated bone marrow chimeras using wild-type and CCR7-deficient mice as recipients and/or donors and analyzed the phenotype of SILT 7-9 wk after reconstitution.…”
Section: Bone Marrow Reconstitution Induces/reverts the Phenotype Of mentioning
confidence: 99%
“…We and others have reported previously that any type of lymphoid aggregation is absent in the intestine of lymphotoxin ␣ mutants (17,26). To further characterize the requirements of other signaling molecules expressed on LTIC for SILT organogenesis, we analyzed the phenotype of SILT in CCR7-deficient and plt/plt mice that lack the CCR7 ligands CCL19 and CCL21-Ser.…”
Section: Ccr7-deficient Mice Display Atypically Hyperplastic Siltmentioning
confidence: 99%
“…Like PP, SILT are absent in the intestines of lymphotoxin-␣, lymphotoxin-␤ and lymphotoxin-␤ receptor-deficient mice (4,18). Moreover, SILT, as well as PP, fail to form in mice lacking the orphan nuclear receptor ROR␥t, which is required for the development and maintenance of LTIC (19).…”
mentioning
confidence: 99%
“…We recently discovered a population of VCAM-1 ϩ stromal cells in both CP and ILF, identifying these cells as candidates for LT␤R-expressing cells involved in the development and maintenance of these structures (20). Because stromal cell populations in CP and ILF had not been previously described, we have characterized the phenotype and origin of these stromal cell populations in detail, focusing on defining what features of these stromal cell networks were dependent on LT signaling.…”
mentioning
confidence: 99%
“…Like other lymphoid tissues, the formation of CP and ILF requires LT␣ 1 ␤ 2 signaling through the LT␤R. Studies using bone marrow (BM) chimera models have shown that the cellular source of LT␣ 1 ␤ 2 used to generate CP and ILF is within the hemopoietic compartment, whereas nonhemopoietic stromal cells provide the LT␤R (19,20).…”
mentioning
confidence: 99%